Magnetosome yield characteristics modeling of acidithiobacillus ferrooxidans in airlift bioreactor using response surface methodology. (February 2023) - He, Shuangjun; Yang, Jiani; Fan, Xinxin; Lu, Dong; Zhang, Shuang; Yan, Lei
Bacterial magnetosomes had been proved to have great application potential in medicine and biotechnology. The objective of the present study was to obtain high yield of magnetosomes from Acidithiobacillus ferrooxidans ( A. ferrooxidans ) BYM in an airlift bioreactor using response surface methodology (RSM). The magnetosomes from A. ferrooxidans BYM were characterized using a transmission electron microscope and scanning electron microscopy. The maximum magnetosome yield of 0.4267 mg/L was achieved at ventilation capacity of 3.6 L/min and gluconic acid concentration of 10 mmol/L at 25 o C. The correlation coefficient (R 2 ) value of 0.8676 of the obtained model suggested a good correlation between the actual and predicted magnetosome yield. The confirmation experiment confirmed that the actual magnetosome yield of 0.391 mg/L obtained were in agreement with the predicted value of 0.398 mg/L. These results suggested that RSM can be employed to find out the optimum conditions for magnetosome formation in airlift bioreactor. Graphical Abstract